Hyperopic shift in obese patients after bariatric surgery: a clinical trial - Chaichian, Shahla; Sheikhvatan, Mehrdad (Bariatric surgical practice and patient care, 2018)
Background: Laparoscopic Roux-en-Y gastric bypass (LRYGB), a common bariatric surgery, may be associated with different ocular effects. The present study aimed to investigate the effect of bariatric surgery on refractive errors. Methods: The clinical study investigated 85 morbidly obese patients, undergoing LRYGB. Ocular examination conducted by one optometrist before and after surgery included measurement of best corrected visual acuity (BCVA) by log minimum angle of resolution (MAR) chart, pupil reactions, slit lamp examination, and visual field determination. Results: The mean body mass index of patients significantly reduced from 46.32 ± 6.90 before surgery to 34.20 ± 10.80 after surgery. The optic examination of patients revealed the difference of postoperational mean BCVA OU log MAR with their previous glasses at 0.063. The changes in the refractive error of patients were as follows: 3 patients (3.5%) had −0.25, 1 patient (1.1%) had −0.5, 1 patient (1.1%) had −0.75 myopic shift, and 75 patients had ...
Gesehen am 08.04.2019